Diplofuranones A and B , two further new 4-monosubstituted 2 ( 3H ) -dihydrofuranones produced by Diplodia corticola , a fungus pathogen of cork oak - Evidente, Antonio; Andolfi, Anna; Fiore, Michele; Spanu, Emanuela (ARKIVOC, 2007)
Two new 4-monosubstituted 2(3H)-dihydrofuranones, named diplofuranones A and B, were isolated from liquid cultures of Diplodia corticola, a plant pathogenic fungus causing a canker disease of cork oak (Quercus suber L.). The same fungus also produces several metabolites such as the diplopyrone, the (3S,4R)-trans- and the (3R,4R)-cis-4-hydroxymellein, the sapinofuranone B and its (S,S)-enantiomer, the well known sphaeropsidins A-C, and the diplobifuranylones A and B. The diplofuranones A and B were characterised, using spectroscopic (essentially NMR and MS techniques) methods, as the 4-[(1E,3E)-5-hydroxyhexadienyl]butan-4-olide and its corresponding 3,4-dihydro side chain derivative. The stereochemistry of the stereogenic secondary hydroxylated carbon of the side chain of diplofuranone A was determined by application of Mosher’s method and proved to be R. Diplofuranone A tested at 0.2 mg mL-1 on non-host plant did not show phytotoxic activity.
Keywords: canker disease; Cork oak; Diplodia corticola; phytotoxic metabolites; Quercus suber L.

Diplofuranones A and B , two further new 4-monosubstituted 2 ( 3H ) -dihydrofuranones produced by Diplodia corticola , a fungus pathogen of cork oak (ARKIVOC, 2007)
Two new 4-monosubstituted 2(3H)-dihydrofuranones, named diplofuranones A and B, were isolated from liquid cultures of Diplodia corticola, a plant pathogenic fungus causing a canker disease of cork oak (Quercus suber L.). The same fungus also produces several metabolites such as the diplopyrone, the (3S,4R)-trans- and the (3R,4R)-cis-4-hydroxymellein, the sapinofuranone B and its (S,S)-enantiomer, the well known sphaeropsidins A-C, and the diplobifuranylones A and B. The diplofuranones A and B were characterised, using spectroscopic (essentially NMR and MS techniques) methods, as the 4-[(1E,3E)-5-hydroxyhexadienyl]butan-4-olide and its corresponding 3,4-dihydro side chain derivative. The stereochemistry of the stereogenic secondary hydroxylated carbon of the side chain of diplofuranone A was determined by application of Mosher’s method and proved to be R. Diplofuranone A tested at 0.2 mg mL-1 on non-host plant did not show phytotoxic activity.

Diplobifuranylones A and B, 5‘-Monosubstituted Tetrahydro-2H-bifuranyl-5-ones Produced by Diplodia corticola, a Fungus Pathogen of Cork Oak (Journal of Natural Products, 2006)
Two new 5?-monosubstituted tetrahydro-2H-bifuranyl-5-ones, named diplobifuranylones A and B (1 and 2), were isolated from the culture filtrates of Diplodia corticola, the causal agent of a canker of cork oak (Quercus suber). The same fungus also produced eight known metabolites, namely, the diplopyrone, (3S,4R)-trans- and (3R,4R)-cis-4-hydroxymellein, sapinofuranone B and its (S,S)-enantiomer, and sphaeropsidins A?C. Diplobifuranylones A and B (1 and 2) were characterized, using spectroscopic and chemical methods, as two diastereomeric 5?-(1-hydroxyethyl)-3,4,2?,5?-tetrahydro-2H-[2,2?]bifuranyl-5-ones. While the relative stereochemistry of the two metabolites (1 and 2) was deduced by NOESY and ROESY experiments, the absolute stereochemistry of the chiral carbon of the hydroxyethyl side chain at C-5?, determined by application of Mosher's method, proved to be S and R in 1 and 2, respectively. Assayed on a nonhost plant, diplobifuranylones A and B did not show phytotoxic activity. In an Artemia salina larvae lethality bioassay neither 1 nor 2 was toxic at the highest concentration tested (300 ?g/mL).
doi: 10.1021/np050393l

Diplobifuranylones A and B, 5‘-Monosubstituted Tetrahydro-2H-bifuranyl-5-ones Produced by Diplodia corticola, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Andolfi, Anna; Fiore, Michele; Spanu, Emanuela; Maddau, Lucia; Franceschini, Antonio; Marras, Francesco; Motta, Andrea (Journal of Natural Products, 2006)
Two new 5?-monosubstituted tetrahydro-2H-bifuranyl-5-ones, named diplobifuranylones A and B (1 and 2), were isolated from the culture filtrates of Diplodia corticola, the causal agent of a canker of cork oak (Quercus suber). The same fungus also produced eight known metabolites, namely, the diplopyrone, (3S,4R)-trans- and (3R,4R)-cis-4-hydroxymellein, sapinofuranone B and its (S,S)-enantiomer, and sphaeropsidins A?C. Diplobifuranylones A and B (1 and 2) were characterized, using spectroscopic and chemical methods, as two diastereomeric 5?-(1-hydroxyethyl)-3,4,2?,5?-tetrahydro-2H-[2,2?]bifuranyl-5-ones. While the relative stereochemistry of the two metabolites (1 and 2) was deduced by NOESY and ROESY experiments, the absolute stereochemistry of the chiral carbon of the hydroxyethyl side chain at C-5?, determined by application of Mosher's method, proved to be S and R in 1 and 2, respectively. Assayed on a nonhost plant, diplobifuranylones A and B did not show phytotoxic activity. In an Artemia salina larvae lethality bioassay neither 1 nor 2 was toxic at the highest concentration tested (300 ?g/mL).
doi: 10.1021/np050393ldoi: 10.1021/np050393lThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Chemical characterization; Diplobifuranylones; Diplodia corticola; metabolites; Phytotoxicity (voyant)

Assignment of the Absolute Configuration of (+)-Diplopyrone, the Main Phytotoxin Produced by Diplodia mutila, the Pathogen of the Cork Oak Decline, by a Nonempirical Analysis of Its Chiroptical Properties† (The Journal of Organic Chemistry, 2004)
The nonempirical assignment of the absolute configuration of (+)-diplopyrone, the main phytotoxin of Diplodia mutila, i.e., an endophytic fungus, widespread in Sardinian oak forests, and considered one of the main causes of cork oak decline, has been approached by two different methods:? (a) the exciton analysis of the circular dichroism (CD) spectrum and (b) the ab initio calculation of the optical rotatory power. Both methods indicate that (+)-diplopyrone is 6-[(1S)-1-hydroxyethyl]-2,4a(S),6(R),8a(S)-tetrahydropyrano[3,2-b]pyran-2-one, so the stereostructure of this important biomolecule is safely determined for the first time. A comparison of advantages and limitations of the two methods of analysis is also presented.
From Duplicate 2 (Assignment of the Absolute Configuration of (+)-Diplopyrone, the Main Phytotoxin Produced by Diplodia mutila, the Pathogen of the Cork Oak Decline, by a Nonempirical Analysis of Its Chiroptical Properties† - Giorgio, Egidio; Maddau, Lucia; Spanu, Emanuela; Evidente, Antonio; Rosini, Carlo)

Diplopyrone, a New Phytotoxic Tetrahydropyranpyran-2-one Produced by Diplodia mutila, a Fungus Pathogen of Cork Oak (Journal of Natural Products, 2003)
A new phytotoxic monosubstituted tetrahydropyranpyran-2-one, named diplopyrone (1), was isolated from the liquid culture filtrates of Diplodia mutila, a plant pathogenic fungus causing a form of canker disease of cork oak (Quercus suber). Diplopyrone was characterized, using spectroscopic and chemical methods, as 6-[(1S)-1-hydroxyethyl]-2,4a,6,8a-tetrahydropyran[3,2-b]pyran-2-one. The absolute stereochemistry of the chiral secondary hydroxylated carbon (C-9), determined by application of Mosher's method, proved to be S. Diplopyrone assayed at a 0.01?0.1 mg/mL concentration range caused necrosis and wilting on cork oak cuttings. On a nonhost plant, tomato, diplopyrone caused brown discoloration or stewing on the stem.

Diplopyrone, a New Phytotoxic Tetrahydropyranpyran-2-one Produced by Diplodia mutila, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Maddau, Lucia; Spanu, Emanuela; Franceschini, Antonio; Lazzaroni, Silvia; Motta, Andrea (Journal of Natural Products, 2003)
A new phytotoxic monosubstituted tetrahydropyranpyran-2-one, named diplopyrone (1), was isolated from the liquid culture filtrates of Diplodia mutila, a plant pathogenic fungus causing a form of canker disease of cork oak (Quercus suber). Diplopyrone was characterized, using spectroscopic and chemical methods, as 6-[(1S)-1-hydroxyethyl]-2,4a,6,8a-tetrahydropyran[3,2-b]pyran-2-one. The absolute stereochemistry of the chiral secondary hydroxylated carbon (C-9), determined by application of Mosher's method, proved to be S. Diplopyrone assayed at a 0.01?0.1 mg/mL concentration range caused necrosis and wilting on cork oak cuttings. On a nonhost plant, tomato, diplopyrone caused brown discoloration or stewing on the stem.
The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 12608876
Keywords: Phytopathogenic fungi; Phytotoxins; relative and/or absolute configuration; structure–activity relationships